Exploring the RNA Gap for Improving Diagnostic Yield in Primary Immunodeficiencies - Lye, Jed J.; Williams, Anthony; Baralle, Diana (Frontiers in Genetics, 2019)
Challenges in diagnosing Primary Immunodeficiency are numerous and diverse, currently whole exome sequencing and whole genome sequencing is only able to produce reliable diagnosis in 25-60% of cases. We assess these problems and demonstrate how RNA investigation technology and literature has experienced great leaps forward in recent years, and can now give unparalleled insight into the elegant inner workings of the cell. We review how investigation into RNA biology can give information regarding the differential expression, mono-allelic expression, and alternative splicing – which have important roles in immune regulation and function. We show how this information can inform bioinformatic analysis pipelines and aid in the variant filtering process, expediting the identification of causal variants – especially those affecting splicing, and enhance overall diagnostic ability. We also demonstrate the challenges, which remain in the design of this type of investigation, regarding technological limitation and biological considerations and suggest potential directions for the clinical applications.